Digital Marketing and Consumer Behavior: Shanker Dev Campus Youth Perception - Khadka, Alisha; Mangrati, Barsha; Khatri, Ashmita; Adhikari, Ambisha; Sharma, Abhinav; KC, Bidhan; Pokharel, Yadav Prasad (NPRC Journal of Multidisciplinary Research, 2024)
The objective of this research was to access the digital marketing landscape from students of SDC. The factor that were taken to consideration for this study were convenience, time saving, website design, motivation, cost , security/trust, communication, social media. This study finds that the emergence of digital marketing is at its peak in current business world. Thus, it is important for organizations to understand the importance of digital marketing from various perspectives to sustain in today’s digital world. The outcomes of the study reflect that the digital platform such as facebook, instagram, snapchat, tiktok and so on has a great influence in attracting customers through their online advertisement. This has made easier for the customer to find and compare all the relevant information about the product they want to purchase. And they find it more convenient and time saving to make online purchase. It has been observed through the study that customers tend to shop more through online platforms during sales, offers and festive seasons.